NJADWALAN PE FASILITAS PENANGANAN PETI KEMAS DI TERMINAL PETI KEMAS SEMARANG - , SORAYA AYU CHUMAIRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Terminal Peti Kemas Semarang (TPKS) is a tool in marine transportation with containers. TPKS deal with queues of trucks when loading operations, but there are also idle cranes are too long. Other than that issue, the movement of trucks in TPKS which is not adjusted for a ship loading operations sometimes make weight to one ship alone. The problems in the TPKS indicate that loading operation is not optimal, it is still possible to perform optimization with existing facilities in TPKS. There are several ways to optimize the arrangement of locations and loading operations of containers in the container yard and container handling facility scheduling. Structuring the location of containers in CY has been optimized by Kirana (2013). To support the results of the determination of the location which is the first stage of optimization in container terminals is necessary for the next optimization is scheduling facilities that move containers from CY to ship by applying the allocation results of previous studies. Facility scheduling is done by mathematical modeling. Optimization mathematical model is built on 9.0 Lingo, Lingo 9.0 but cannot finish in time optimization that can be tolerated. Thus built the model using genetic algorithm method with the aim of minimizing the makespan is used for scheduling facilities. The model was built using MATLAB R2012b software. The model will produce a combination of the use of the facilities quay cranes, trucks, and yard cranes. The model is built in accordance with the treatment for ships that have only one purpose. The model can be completed for a ship scheduling by considering the performance of the truck just for one ship, the exact number RTG and container location optimal distance. The results of operations scheduling visits from container loading time to ship. Comparison of model results with actual time is the total time reduced by 2826.34 minute boat